Methodological Challenges in Online Trials - Murray, Elizabeth; Khadjesari, Zarnie; White, Ian R; Kalaitzaki, Eleftheria; Godfrey, Christine; McCambridge, Jim; Thompson, Simon G; Wallace, Paul (JMIR Publications, 2009)
Health care and health care services are increasingly being delivered over the Internet. There is a strong argument that interventions delivered online should also be evaluated online to maximize the trial's external validity. Conducting a trial online can help reduce research costs and improve some aspects of internal validity. To date, there are relatively few trials of health interventions that have been conducted entirely online. In this paper we describe the major methodological issues that arise in trials (recruitment, randomization, fidelity of the intervention, retention, and data quality), consider how the online context affects these issues, and use our experience of one online trial evaluating an intervention to help hazardous drinkers drink less (DownYourDrink) to illustrate potential solutions. Further work is needed to develop online trial methodology.